1997
DOI: 10.1016/s0022-5347(01)64950-4
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Wall Sling: Long-Term Outcome Analysis of Factors Contributing to Patient Satisfaction and Surgical Success

Abstract: The vaginal wall sling represents an excellent option for the treatment of genuine stress incontinence and an acceptable option of intrinsic sphincteric deficiency. Patient perception and satisfaction remain closely associated with presence or resolution of postoperative urge incontinence. However, prediction of postoperative urge incontinence remains a challenge and should be considered when counseling patients preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 9 publications
0
14
0
3
Order By: Relevance
“…Other studies on the correlation between VLPP and the outcomes of anti-incontinence procedures also fail to demonstrate the value of VLPP as a predictor of surgical outcomes, such are the studies of Mikhail and Rosa [2000] on the surgical outcome after retropubic urethropexy for GSUI and the study of Kim et al [1997] on the results of collagen injections. Other opinions do exist, and preoperative VLPP was found to be correlated with resolution of stress incontinence, although not with patient satisfaction, after vaginal wall sling as reported by Litwiller et al [1997]. Surgical outcome measures examined included stress incontinence, urge incontinence, and frequency-urgency symptoms with patients categorized to three groups in each symptom complex: symptoms resolved/improved (þ1), no change in symptoms (0), and worsened/de-novo appearance of symptoms (À1).…”
Section: Discussionmentioning
confidence: 88%
“…Other studies on the correlation between VLPP and the outcomes of anti-incontinence procedures also fail to demonstrate the value of VLPP as a predictor of surgical outcomes, such are the studies of Mikhail and Rosa [2000] on the surgical outcome after retropubic urethropexy for GSUI and the study of Kim et al [1997] on the results of collagen injections. Other opinions do exist, and preoperative VLPP was found to be correlated with resolution of stress incontinence, although not with patient satisfaction, after vaginal wall sling as reported by Litwiller et al [1997]. Surgical outcome measures examined included stress incontinence, urge incontinence, and frequency-urgency symptoms with patients categorized to three groups in each symptom complex: symptoms resolved/improved (þ1), no change in symptoms (0), and worsened/de-novo appearance of symptoms (À1).…”
Section: Discussionmentioning
confidence: 88%
“…Although some authors report autologous slings usually fail within the first 3 months after surgery [26] because of suture breakage, incorrect sling placement and tying the sling too loosely, a retrospective meta-analysis [27] reported that autologous slings have an average cure rate of 83% more than 4 years after surgery. Surprisingly, data on recent outcomes reveal a cure rate of 46-55% after 4 years [18,28,29,30]. Implicit in some reports is the progressive decrease in cure rates for autologous slings with longer follow-ups.…”
Section: Discussionmentioning
confidence: 99%
“…Ce sont les techniques dérivées de la FV proposée par Raz et al en 1989 [2]. Ces procédés, peu répandus en France [5], sont presque exclusivement utilisés par les chirurgiens urologues anglo-saxons [11][12][13][14]. Bien que ces différentes techniques répondent globalement au même principe, les résultats fonctionnels et les taux de complication varient beaucoup selon les auteurs.…”
Section: Discussionunclassified
“…[3,14]. Les complications rapportées sont nombreuses [2][3][4][5][12][13][14]. Elles sont liées pour la plupart au principe même de ces interventions (dissection vésico-vaginale, abord aveugle de l'espace de Retzius et mise en tension de la fronde) et plus rarement à l'utilisation du tissu vaginal.…”
Section: Discussionunclassified
See 1 more Smart Citation